2009
DOI: 10.4103/0970-1591.57912
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, and voided volume dependency of peak urinary flow rate and uroflowmetry nomogram in the Indian population

Abstract: Objectives:The objective of this study was measurement of urine flow parameters by a non invasive urodynamic test. Variation of flow rates based on voided volume, age, and gender are described. Different nomograms are available for different populations and racial differences of urethral physiology are described. Currently, there has been no study from the Indian population on uroflow parameters. So the purpose of this study was to establish normal reference ranges of maximum and average flow rates, to see the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(100 citation statements)
references
References 18 publications
14
86
0
Order By: Relevance
“…[9][10][11][12] There is also little evidence with regards to the usefulness and effectiveness of UF for different conditions in children. 13 UF has been used commonly in patients with VD and postoperative hypospadias and our data support these indications. Diagnosis of VD in children can be a challenge to pediatric urologists.…”
Section: Discussionsupporting
confidence: 75%
“…[9][10][11][12] There is also little evidence with regards to the usefulness and effectiveness of UF for different conditions in children. 13 UF has been used commonly in patients with VD and postoperative hypospadias and our data support these indications. Diagnosis of VD in children can be a challenge to pediatric urologists.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the VQI seems to be a more universal concept since our final definition is quadratic one similar to that of Von Garrelts (Caucasian). Another limitation is not incorporating age which is another important determinant of flow rates. Kumar et al found a weak correlation between flow rates and age both below and beyond 50 years of age ( R 2 = 0.02, P = 0.012 and R 2 = 0.09, P = 0.001, respectively). In our study of men aged 18–50 years, the correlation between flow rates and age was weak ( R 2 = 0.019, P = 0.001 for cQ max and R 2 = 0.017, P = 0.002 for cQ ave ).…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Younger patients demonstrate more robust flow due to stronger bladder contractions and less prostatic obstruction. In this study, both Q m and Q m -Q a demonstrated superior predictive capability in detecting stricture recurrence in patients ≤40 years of age (AUC of 0.9224 and 0.9324, respectively) compared to patients >40 years of age (AUC of 0.7661 and 0.7484, respectively).…”
Section: Discussionmentioning
confidence: 99%